The Influence of the Use of Three-Dimensional Media on Student Learning Outcomes on Building Spatial Materials in Class V SD Negeri Peace Aceh Tamiang - Majidah, Selvi -; Israwati, Israwati; Fauzi, Fauzi (Elementary Education Research, 2023)
Media is used to support students in understanding new knowledge or skills acquired. The function of three-dimensional media in geometric learning activities is very supportive for teachers and students. The purpose of this research is to find out whether students' learning outcomes on geometric materials are influenced by the use of three-dimensional media in class V SD Negeri Peace Aceh Tamiang. This research uses a quantitative approach with a quasi-experimental research type. The research subjects consisted of 20 fifth grade students, with 8 boys and 12 girls. The method of data was collected by using a test of 10 multiple choice questions and 5 short answer questions, then analyzed using the t-test statistical formula at the 5% level. The research results obtained evidence that the use of three-dimensional media has a significant effect on student learning outcomes, this is based on the significance level = 0.05 while the degrees of freedom = (n1) = (20-1)=19. So with the distribution index t (can be seen in the attachment to the t test) the value of dk = 19 is obtained or the value of t is 0.95 (19) = 1.73 while tcount = 19.42. Obtained data that tcount ttable then reject Ho thus accept Ha. The average score of students is 76. As many as 17 students have successfully completed taking examples of learning geometric materials with three-dimensional media products. This completeness supports the researcher's hypothesis that the use of three-dimensional media has an impact on student learning outcomes. Therefore, it can be concluded that three-dimensional media is used to increase student learning outcomes, especially spatial material in class V SD Negeri Aceh Tamiang Peace is very effective.